A Study on Automatic Platform Gate (APG) and Platform Screen Door (PSD) Alternative Design for Kuching Urban Transportation System (KUTS) Line using Software AutoCAD - Tang, Chong Woo; Mahyeddin, Mohd Eizzuddin (Progress in Engineering Application and Technology, 2023)
Automatic Platform Gate (APG) and Platform Screen Door (PSD) at platform station build a barrier to separate passengers from falling onto the rail track to ensure passenger safety. However, the high initial cost and complex installation of APG system made KUTS only implement to 2 platform station (Hikmah Exhange main station, Simpang Tiga interchange station) for KUTS line phase 1. SWOT analysis was carried out to identify the alternative design solution for platform stations without APG in KUTS line phase 1. Future expansion work, precise stopping point at platform station, and high initial cost identified as major problem issues of APG preliminary design KUTS phase 1. The 3D model of alternative design of APG and PSD called wire screen door was developed and produced using software AutoCAD. Then, software Inventor used to perform Finite Element Analysis (FEA), stress analysis on the wire screen door supporting pillars. The displacement of the supporting pillars measured as a result of stress. The wire screen door system produced can reduce or eliminate the weaknesses of APG and PSD preliminary design KUTS phase 1.